Exploring research data in Indian institutional repositories. Issue 2 (1st April 2014) - Hanief Bhat, Mohammad
Abstract : Purpose: – The purpose of this paper is to explore various types of research materials in Indian institutional repositories. Design/methodology/approach: – The repositories are identified from the Registry of Open Access Repositories (ROAR). The repository sites were visited to collect the data necessary for the study. Findings: – The present study reveals that barring a few repositories the collections of most of the repositories are very low. The percentage of archived materials is high for journal papers, and moderate for conference papers/thesis. However it is very low for preprints/working papers, teaching resources and patents. Originality/value: – The study provides an overview of archived material in institutional repositories in India.